Cross-sectional study of dental cellulitis and associated factors in Kinshasa City, Democratic Republic of the Congo - Adelin Baudoin NZUDJOM FOCHE; Paul BOBE ALIFI LETA; Trésor RAMAZANI HARUNA; Charles MFUTU MANA; Jean-Paul SEKELE ISOURADI BOURLEY; Hippolyte SITUAKIBANZA NANI-TUMA; Moïse MONIZI MAWANU; Dan MULUMBA NKELENDA; Jean-Pau (Orapuh, Inc., 2023)
Introduction The prevalence of dental cellulitis remains high in developing countries like the Democratic Republic of the Congo, and its epidemiology varies by region and country. Therefore, they represent a significant public health problem. Purpose The purpose of this cross-sectional study was to assess the status of dental cellulitis in the communities of Kinshasa to improve its management. Methods An analytical cross-sectional study was conducted within the healthcare system of the Archdiocese of Kinshasa through the networks of the Bureau des Œuvres Médicales, specifically at the grassroots ecclesial communities, from March 1 to March 31, 2020, and then from September 1 to December 31, 2020. The study population consisted of individuals with oral and dental pathologies who responded to the Community Health Workers' call for screening. Results A total of 512 individuals suffering from oral and dental pathologies were included in the study, of which 176 had dental cellulitis. The prevalence of dental cellulitis was 34.4%. Low socioeconomic status, poor oral hygiene, diabetes, alcohol exposure, self-medication with antibiotics and NSAIDs, and traditional medicine were factors associated with its occurrence. Dental causes accounted for 86.4% of dental cellulitis cases, with dental caries and its complications being the most incriminated (79.6%). Conclusion Dental cellulitis is common among oral and dental pathologies in the communities of Kinshasa. Dental caries and its complications are the primary determinants, and low socioeconomic status, poor oral hygiene, NSAIDs, antibiotics, diabetes, alcohol exposure, and traditional medicine are associated factors in their occurrence. This study will serve as a database to help policymakers better tailor strategies to combat oral health conditions in general, and dental cellulitis.